Budaya Kerja Adaptif sebagai Strategi Organisasi dalam Menghadapi Perubahan Digital yang Pesat - M. Farrel; Maiza Fikri (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
The rapid pace of digital change requires organizations to build an adaptive work culture in order to maintain long-term competitiveness and operational effectiveness. This study uses a descriptive qualitative approach with a literature review of scientific journals, books, and organizational reports related to digital transformation and human resource development. The analysis focuses on adaptive leadership strategies, competency development, and digital technology integration to strengthen adaptive culture. The results show that adaptive leadership is the main foundation for building employee values, motivation, and commitment to respond to technological changes, while adequate digital technology and infrastructure support flexibility, collaboration, and continuous learning. Challenges such as resistance to change, digital competency gaps, and cybersecurity can be minimized through internal policies, continuous training, and holistic change management. This study confirms that an adaptive work culture not only accelerates technology adoption but also strengthens organizational resilience and creates long-term competitive advantage in the digital era.